3 ′-5 ′ crosstalk contributes to transcriptional bursting - Cavallaro, Massimo; Walsh, Mark D.; Jones, Matt; Teahan, James; Tiberi, Simone; Finkenstädt, Bärbel; Hebenstreit, Daniel (Genome Biology, 2021)
Background Transcription in mammalian cells is a complex stochastic process involving shuttling of polymerase between genes and phase-separated liquid condensates. It occurs in bursts, which results in vastly different numbers of an mRNA species in isogenic cell populations. Several factors contributing to transcriptional bursting have been identified, usually classified as intrinsic, in other words local to single genes, or extrinsic, relating to the macroscopic state of the cell. However, some possible contributors have not been explored yet. Here, we focus on processes at the 3 ′ and 5 ′ ends of a gene that enable reinitiation of transcription upon termination. Results Using Bayesian methodology, we measure the transcriptional bursting in inducible transgenes, showing that perturbation of polymerase shuttling typically reduces burst size, increases burst frequency, and thus limits transcriptional noise. Analysis based on paired-end tag sequencing (PolII ChIA-PET) suggests that this effect is genome wide. The observed noise patterns are also reproduced by a generative model that captures major characteristics of the polymerase flux between the ends of a gene and a phase-separated compartment. Conclusions Interactions between the 3 ′ and 5 ′ ends of a gene, which facilitate polymerase recycling, are major contributors to transcriptional noise.